Prevalence and risk factors of bacterial vaginosis among female sex workers in Surakarta - Hastuti, Rini; Yuliarto, Danu; Triana, Agung; Damayanti, Willa; Irfanti, Rakhma Tri; Mardiana, Mardiana; Dewi, Putti Fatiharani; Aliwardani, Ambar; Abas, Ervianti; Sulistyo, Sulistyo; Mawardi, Prasetyadi; Ellistasari, Endra Yustin (Journal of General - Procedural Dermatology and Venereology Indonesia, 2019)
Background: Bacterial vaginosis (BV) is the most common vaginal infection in women of reproductive age and increases the risk of acquiring human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs). Data regarding the association between sexual activity and BV acquisition is contradictory. Thus, tracking the prevalence and associated risk factors of BV among female sex workers (FSWs) is necessary to improve our understanding and control of STDs and the HIV epidemic. Methods: The subjects of this study were FSWs in Surakarta. This study adopted a cross-sectional design, and diagnosis was established using Amsel criteria. Interviews were conducted using questionnaires to collect data of risk factors, including demographic factors (age, education level, daily income, marital status, location of sex), sociologic factors (age of first intercourse; age of first FSW encounter; duration of work as an FSW; number of clients/day; condom, contraceptive, and vaginal douching use; violence experienced as an FSW; smoking habits; alcohol consumption; and drug use), and knowledge factors (knowledge of STDs and HIV). Statistical analysis was performed by using bivariate analysis. Results: We interviewed 175 FSWs with an average age of 40.66 years. BV was detected in 28 subjects (16%). Risk factors associated with BV include alcohol (p = 0.022) and drug use (p = 0.022). Conclusion: Other than routine screening for STDs and HIV, FSWs should be encouraged to participate in prevention programs aiming to regulate alcohol and drug use to decrease the incidence of BV infection.